1987
DOI: 10.1332/251569298x15668907344316
|View full text |Cite
|
Sign up to set email alerts
|

The Social Cost of Rent-Seeking: First Estimates

Abstract: Sin dalle prime formulazioni del problema della ricerca di rendite parassitarie (rent-seeking) gli studiosi si sono concentrati sugli aspetti teorici, senza verificarne empiricamente il costo sociale.Viene qui tentata una prima quantificazione di questo fenomeno, anche se le difficoltà di misurazione fanno ritenere che le stime così ottenute costituiscano soltanto una prima approssimazione.A questo fine viene effettuato un confronto fra attività bancaria, considerata come l’indicatore del livello di produzion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…al. 1991) or banking activity (Laband and Sophocleus 1988) are wholly productive. The improbability of such a sharp occupational dichotomy between unproductive and wealth-creating activities suggests that the extent to which lawyering is growth-dampening will depend upon the relative unproductiveness of lawyering compared to other occupations (Epp 1992: 594).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 1991) or banking activity (Laband and Sophocleus 1988) are wholly productive. The improbability of such a sharp occupational dichotomy between unproductive and wealth-creating activities suggests that the extent to which lawyering is growth-dampening will depend upon the relative unproductiveness of lawyering compared to other occupations (Epp 1992: 594).…”
Section: Discussionmentioning
confidence: 99%
“…Datta and Nugent (1986) then produced an empirical study of 'adversary activity' which provided tentative confirmation that legal activities were likely to lower profits and investment, concluding that countries needed to reduce the numbers of individuals involved in resolving conflicts, thereby freeing up highly qualified people for more economically productive activities. Laband and Sophocleus (1988) used the number of practicing lawyers as a proxy for the level of politico-legal rent-seeking, calculating that the associated economic loss came to US$ 902.5 billion, equivalent to 22.6 per cent of US 1985 nominal GNP (or US$ 2.9 million per lawyer). Murphy et al (1991) extended the analysis to 91 countries and used data on college law enrolments as an indicator of the talent allocated to rent-seeking (engineering enrolments reflecting entrepreneurial endeavour).…”
Section: The Unproductive Labour Argumentmentioning
confidence: 99%
“…69-92. Laband, D. N., Sophocleus, J. P. (1988). The social cost of rent-seeking: First estimates // Public Choice, 58(3), 269-275.…”
Section: список литературыmentioning
confidence: 99%
“…Following this, the social cost of lobbying was measured. For example Laband and Sophocleus (1988) showed that profit-seeking drastically reduced the growth of the American GNP by 22.6 percent for the year 1985 (also see Zimmermann, 2009a on this point, andDesai andOlofsgard, 2011, for the specific case of developing countries).…”
Section: Classical Analysis Of the Effects On Social Welfarementioning
confidence: 99%